HISTORY OF PRINTING IN TURKESTANT (UZBEKISTAN). - Nilufar Namazova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article covers the history of the first publishing houses and printing works established in Turkestan (Uzbekistan).